Sungai Sebagai Wadah Awal Munculnya Peradaban Umat Manusia - Nurlidiawati Nurlidiawati (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
Civilization in terms of language aspects. In English called civilizations that Significantly improve the behavior is rude or impolite (civilize). While in Arabic terms with the same meaning as Madaniah civilization, hadarah, and tamaddana the which means the act opens airport or city and act refine manners. While in Chinese civilization called wenming the which means bright, bright, and luminous. Several of the meanings of civilization, then interpreted by scientists so comes the understanding of different civilizations , but the essence of civilization are the parts of a culture that is more beautiful, smooth, and high value. So civilization is the result of human thought the which is manifested through attitudes, ethics or aesthetics realistically. In this case the bias civilization tangible science, economics, the field of sports, the arts, politics or other fields. Before you reach civilization, Humans must first go through a phase called culture. Culture at its core is the result of human creativity and sense of initiative. Humans are creatures of God are enhanced with reason, that the reason this man is Able to change from the primitive to the modern and others. A human group or community WHO have Reached a on certain stage of culture, and have developed meaningful community Achieved have higher levels of civilization with traits like mastery of science, technology, arts, and others. Between man and civilization are two sides that can not be separated. The which includes the central region of human civilization in the past in this paper is the valley of the Nile, Euphrates, Tigris, Indus or Indus, and Huang Ho. In the valleys it is all human activity that centered around life. Because in addition to drinking, bathing, irrigation source, and wash, on the river there are fish and other animals are a source of human life. Activities for the sake of the activity that creates a civilization in the valleys